Acetogen Communities in the Gut of Herbivores and Their Potential Role in Syngas Fermentation - Chunlei Yang (Fermentation, 2018)
To better understand the effects of host selection on gut acetogens and their potential role in syngas fermentation, the composition and hydrogenotrophic features of acetogen populations in cow and sheep rumens, rabbit ceca, and horse feces were studied. The acetogens detected in horses and rabbits were more phylogenetically diverse than those in cows and sheep, suggesting that the host species plays an important role in shaping gut acetogen populations. Acetogen enrichments from these animals presented good capacities to use hydrogen, with acetate as the major end product. Minor propionate, butyrate, and isovalerate were also produced. During 48 h of incubation, acetogen enrichments from horse consumed 4.75 moles of H2 to every 1 mole of acetate—significantly lower than rabbits, cows, and sheep (5.17, 5.53, and 5.23 moles, respectively) (p < 0.05)—and produced significantly more butyrate (p < 0.05). Enrichments from cows and sheep produced significantly higher amounts of propionate when compared to rabbits or horses (p < 0.05); enrichments from sheep produced the highest amounts of isovalerate (p < 0.05). These short chain fatty acids are important precursors for the synthesis of biofuel products, suggesting that gut contents of herbivores may be promising sources for harvesting functional acetogens for biofuel production.